Pembelajaran Materi Nilai Tempat Bilangan Berbasis ICARE (Introduction, Connection, Application, Reflection dan Extension) Terintegrasi Islam di Kelas II SD/MI - Adelia Wardatul Laily; Fazat Arifatul Ulfah; Nadia Farah; Beatrica Aulia Rahmawati (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
Mathematics is often considered a scary and difficult subject, many students do not like mathematics. This happens because the initial concept of the material is not fully mastered by students, because students will have difficulty learning higher material concepts if they do not have a strong understanding of the basic concepts of simple material, in this study is the place value of numbers. Students who have a strong understanding of place value material will be facilitated in mastering further, more complex material. Place value material is important to understand before entering into more complex material levels such as addition, subtraction, multiplication and division. The purpose of this study was to determine the development of place value material integrated with Islam based on ICARE model at grade II SD/MI. This study used a qualitative research method with a library research approach. The results of this study are place value material developed using the ICARE model integrated with Islam so that students are able to experience meaningful learning integrated with Islam and understand mathematical concepts.